Theoretical approach to the concept of Person-Centered Care: An integrative literature review (Research, Society and Development, 2023)
Integrative literature review study related to the concept of person-centered care. The objective was to identify the production of scientific articles on the theme, recognizing central elements of the concept, characteristics of users and health services that develop this type of care. It took place from January 2014 to December 2019, in the LILACS, PUBMED and Scielo databases. The sample consisted of 12 articles. Person-centered care has a multidimensional concept, not yet well defined in the scientific literature. The central elements of the concept were identified: care that respects people's preferences; that includes people in clinical decisions and that requires professional empathy, to improve communication between user-professionals and increase the bond for adherence to therapy. It was identified in the articles that the study sites were primary care units, referral services and hospitals that served the elderly, pregnant women and patients with chronic conditions.